Метод профілактики ротації торичних інтраокулярних лінз з використанням стандартного капсульного кільця - Завгородня, Наталія Григорівна; Новікова, Валерія Юріївна; Zavgorodnya, N. H.; Novikova, V. Yu. (My University, 2024)
Мета. Визначення ефективності застосування методу профілактики ротації торичної інтраокулярної лінзи після факоемульсифікації катаракти за допомогою імплантації капсульного кільця на очах з рогівковим астигматизмом. Rotation of TIOL after phacoemulsification of cataracts is accompanied by a significant decrease in visual acuity and requires repositioning of IOL. Purpose: to evaluate the effectiveness of the method of preventing the toric intraocular lens rotation after phacoemulsification of cataracts by implantation of a standart capsule ring in the eyes with corneal astigmatism. 43 patients (59 eyes) were examined, who underwent surgery by phacoemulsification of cataracts with implantation of toric intraocular lenses (TIOL) to correct corneal astigmatism. The first group - 26 patients (31 eyes), what TIOL implantation according to standard techniques. The second group - 18 patients (28 eyes) who were operated on according to our proposed prevention method of TIOL rotation. 6 months after surgery, the average deviation TIOL in the second group was 2.14±0.4 degrees (max - 6°, min - 0°), which did not significantly impair visual function. The use of a standard capsular ring over the implanted TIOL to prevent its rotation according to the developed method allows to achieve rotational stability of the implanted lens. The developed method can be recommended for use in practice.
Prevention method of toric intraocular lens rotation using a standard capsule ring